Bibliometric Analysis of Human Resource Management Research in the Field of Health Services during the COVID-19 Pandemic: 2019-2023 Study - Jati, Hendra (SMARTINDO, 2023)
Purpose – This paper presents and discusses the mapping of the research landscape in the field of Human Resource Management (HRM) in the field of health services, especially during 2019-2023. This research was conducted through bibliometric analysis of major journals and publications. Through this approach, we analyze the patterns, trends, and characteristics of publications related to HRM in the health care sector that have been published. Design/methodology/approach – Bibliographical data was obtained from Scopus database sources, including leading journals and trusted publications in the field of HRM. We analyze the country where the research was conducted, local and global citation analysis. In addition, we also analyze citation patterns, map collaboration networks between authors, and identify the most dominant research themes in the HRM field over the last 5 years using VOSviewer software. Originality - Findings and Discussion – The results of research by mapping using the keywords